New standards for training mental health professionals at the postgraduate level. - Zubatiuk, Оксана; Pyliagina, Галина (Psychosomatic Medicine and General Practice, 2023)
Abstract. The article deals with the issues of quality training of professionals in the field of mental healthcare, which is an urgent problem in the context of the war in Ukraine. Postgraduate medical education is an important stage of their training and is included in the ongoing professional development of psychiatrists as a process of continuous enhancement of professional knowledge and skills. Specialization is one of the types of training for mental health professionals. Taking into consideration the complex challenges of the current stage of postgraduate education development in Ukraine and the new standards of higher education introduced in our country, the academic staff of the Department of Psychiatry, Psychotherapy and Medical Psychology of Shupyk National Healthcare University of Ukraine has developed an educational programme of specialization in Psychiatry. The aim of this programme is to train professionals capable of solving complex tasks and innovative problems in the field of mental healthcare, as well as preventive mental health, psychodiagnostics, psychocorrection and treatment of mental health-related diseases which are characterized by uncertainty of conditions and requirements and may require research and/or innovation. Its main task is to develop key competencies in the field of mental healthcare. The programme consists of educational and practical components and is designed for 900 hours, which is 30 ECTS credits. There are 202 hours of independent work, which is 22% of the total. This should facilitate more active involvement of participants of the educational process in learning, as well as delegate the responsibility for acquiring knowledge and skills to them. An important component of the programme is the list of mandatory competences (integral, general and professional) that doctors must acquire during the learning cycle and that will determine their ability to successfully carry out professional activities. Programme learning outcomes, as well as matrices of compliance with the defined results, competences and components of the educational programme have been introduced to determine the effectiveness of the educational process. Thus, this educational programme of specialization in Psychiatry reflects modern changes in the training of professionals at the postgraduate level of medical education.